2018
DOI: 10.15376/biores.14.1.688-699
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-performance activated carbons using bamboo through one-step pyrolysis

Abstract: One-step pyrolysis is a promising thermal degradation process that has a fast reaction rate and high energy efficiency. In this study, high performance bamboo activated carbon was successfully prepared by one-step pyrolysis with different pyrolysis times (2.5 h, 5 h, and 10 h). Using a high pyrolysis temperature of 1050 °C, the specific surface area was remarkably increased to 2348 m2/g, which was substantially higher than the findings reported previously by other studies. The mesopore ratio was increased to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Bamboo charcoal was synthesized from 4 types of Bamboo, Javanese, Apus, Yellow and Ori bamboo by heating process and carried using 2 methods, ordinary charcoal and pyrolysis (Liu et al, 2010;Smith et al, 2019). The each bamboo were cut into tiny size and heated in a furnace with temperatures as 400 o C for 2 hours.…”
Section: The First Stage Is Synthesis and Activation Bamboo Charcoalmentioning
confidence: 99%
“…Bamboo charcoal was synthesized from 4 types of Bamboo, Javanese, Apus, Yellow and Ori bamboo by heating process and carried using 2 methods, ordinary charcoal and pyrolysis (Liu et al, 2010;Smith et al, 2019). The each bamboo were cut into tiny size and heated in a furnace with temperatures as 400 o C for 2 hours.…”
Section: The First Stage Is Synthesis and Activation Bamboo Charcoalmentioning
confidence: 99%
“…Previous literature has explored the adsorption capabilities of carbon fber aerogel derived from natural bamboo fbers, highlighting the potential of bamboo in capturing oils and organic solvents [70][71][72][73]. Studies have also reported successful dye removal using bamboo-based activated carbons [74][75][76][77], bamboo-based biochar [78,79], and carbonized bamboo leaf powder [80].…”
Section: Introductionmentioning
confidence: 99%
“…Forests 2023, 14, x FOR PEER REVIEW 2 of 24 encompassing applications in paper production, bamboo toothpick manufacturing, reusable utensils, and much more [9]. In addition to its practical applications, bamboo plays a crucial role in the chemical industry, including pollutant treatment [10], serving as an electrode material [11], contributing to the generation of bioenergy [12], etc. This is attributed to the exceptional properties of bamboo, which impart distinct characteristics to its derivatives, thereby broadening their range of applications.…”
Section: Introductionmentioning
confidence: 99%